Analisis Finansial Pengembangan Industri Sagu Melalui UMKM di Distrik Tomu Kabupaten Teluk Bintuni - Ardha Puspita Sari (JFRES Journal of Fiscal and Regional Economy Studies, 2018)
Tomu District's economy in general still adheres to the traditional system. Economic development efforts in Tomu District from traditional to modern system can be started by developing a home industri. One resource that can be utilized to develop the home industri in Tomu District is sago. Sago forest area in this district is wide enough, that is 51,804 ha. The purpose of this research is to figure out the market opportunity and financial feasibility of the sago industri development through UMKM in Tomu District. Based on the analysis, the projection of wet sago production of home industri in Tomu District is 320 Kg/trunk. The industri is expected to process 1 trunk of sago in a full day operation. In average, the industry can process approximately 20 trunks of sago per month. With the average selling price in Bintuni Regency is Rp. 15.000/Kg wet sago, then the average income earned in one production process is projected to reach Rp 39.474.417. The projection results of B/C ratio, NPV and IRR indicated that sago processing industry in Tomu District was financially feasible. It is then expected that the development of sago home industry in Tomu District can be operated in accordance with the projected price.